How well do tree plantations comply with the twin targets of the Clean Development Mechanism? The case of tree plantations in Tanzania - Solveig Glomsrød; Gang Liu; Taoyuan Wei; Jens B. Aune (Statistics Norway, Research Department, 2008)
This paper studies the effect of a CDM tree-planting project on carbon sequestration and urban and rural income distribution, taking economy-wide impacts into account. Carbon sequestration in agricultural soil is considered in addition to the carbon in the tree farm itself. The study points to that project designs that raise the general investment level may add substantially to the project's carbon capture by stimulating the productivity of agriculture, thus binding more carbon in soil. As demand for crops is rising, the mode of agricultural production turns more intensive and improved plant growth leaves more plant residues for uptake as soil organic carbon. As for the income effect, the non-poor benefit more than the poor in economic terms, except when the project is hosted by the rural poorest. Foreign owned projects withdrawing the project surplus may turn out to reduce the income of urban poor and does not enhance agricultural productivity and beyond-project carbon sequestration.
Keywords: D58; O13; Q52; Q56; Q58; 330; CDM; afforestation; poverty reduction; CGE; Tanzania